Rituals, Beliefs, And Social Bonds: A Durkheimian Study of The Malamuthan Religious Structure (International Journal of Environmental Sciences, 2025)
This research paper explores the religious structure of the Malamuthan community in Nilambur, of Malappuram district in Kerala, utilizing Emily Durkheim's theoretical framework on religion as a lens for analysis. Durkheim's theory, which views religion as a social institution that fosters collective conscience and cohesion, helps to explain the Malamuthan people's traditional and changing religious practices. Furthermore, it investigates how this religious structure which involves beliefs, rituals, rites, ceremonies and social organization, is impacted by a variety of elements such as socio-cultural, economic, and external influences, as well as the community members' long-standing religious connection to their culture. Preliminary analysis of the collected data reveals four prominent themes underpinning this connectedness: Land, Deities and Ancestors, Taboos and Morals, Transference of Knowledge, and social cohesion and ritual dance. Methodologically, this research employs a qualitative approach incorporating ethnographic techniques such as participant observation, semi-structured and in-depth interviews with community members and the analysis of religious rituals. The research findings reveal the enduring religious connectedness of the community members amidst prevailing situation and the role of religious structure and society in fostering the individual growth and thereby the communal bonds as well.